Assessment of pharyngeal airway space in patients with different maxillofacial skeletal abnormalities using cone beam computed tomography - Shraddha Jugade; Easwaran Ramaswami; Sonali Kadam; Amit Ramchandani; Hemant Umarji (Amaltea Medical Publishing House, 2024)
Background. The patency of the pharyngeal airway has a far-reaching impact on craniofacial development. Conversely, the position of the maxillofacial skeletal components in certain disorders may lead to a compromised airway. Therefore, the evaluation of the airway is an essential step in treatment planning. Objectives. The basic aim of this study was to measure the pharyngeal air space volume in the patients with maxillofacial skeletal abnormalities (like Class II, Class III malocclusion, TMJ Ankylosis, Condylar abnormalities and Syndromic cases) and those without any skeletal abnormalities. The objectives were to assess the Linear, Cross-sectional, and Volumetric dimensions of the pharyngeal airway in patients with and without maxillofacial skeletal abnormalities. (Study and Control group) Materials and methods. The Study group included 49 patients with maxillofacial Skeletal abnormalities like Class II and Class III malocclusion, Temporomandibular Joint Ankylosis, Condylar abnormalities, Syndromic cases. 49 Control group patients did not present with any skeletal abnormalities. The Linear, Cross-sectional, and Volumetric dimensions of the pharyngeal airway in the Study group and Control group were calculated and compared within the groups. Statistical Analysis: Unpaired t -test, ANOVA test and Tukey's Post Hoc analysis test were for the data analysis of the above study. Outcomes. The Anteroposterior dimension of the airway at the Superiormost level was found to be significantly greater in Class II (p-value-0.039), Class III (p-value-0.002), and Control groups (p-value <0.001) when compared with the TMJ Ankylosis group. The Volume and Cross-sectional area of the airway at the most constricted level of the airway was found to be significantly greater in Class III (p-value <0.001) and Control group (p-value 0.013, 0.003) respectively when compared with the TMJ Ankylosis group. Conclusions. The pharyngeal airway was narrowest anteroposteriorly at all three levels (Superior-most, Most constricted, and Inferior-most levels) in the TMJ Ankylosis group and widest in the Class III group. The least cross-sectional area was found in the TMJ Ankylosis group whereas the greatest was found in the Class III group. The airway volume in the TMJ Ankylosis group and Class II group is significantly lesser than that of the Control group.